Strengthening the Governance and Performance of State-Owned Financial Institutions - Scott, David H. (World Bank, Washington, DC, 2012)
Corporate governance arrangements define the responsibilities, authorities and accountabilities of owners, boards of directors, and executive managers of a company. Good corporate governance is as important for state financial institutions as for private sector companies. Many of the problems that commonly afflict state financial institutions can be associated with, if not attributed directly to, weaknesses in corporate governance. This note draws on guidelines recently published by the OECD and the Basel Committee for Banking Supervision to compile a comprehensive corporate governance evaluation framework relevant to state-owned commercial and development finance institutions. It highlights aspects of this framework that are considered to be of particular importance to state financial institutions by citing innovative practices in a number of countries. Finally, it presents a detailed case study of the governance arrangements in place at the Development Bank of Southern Africa.